2010
DOI: 10.1007/s00330-010-1964-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy-CT of hypervascular liver lesions in patients with HCC: investigation of image quality and sensitivity

Abstract: Low-kVp images of dual-energy datasets are more sensitive in detecting hypervascular liver lesions. However, this increase in sensitivity goes along with a decrease in the subjective image quality of low-kVp images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 30 publications
(40 reference statements)
2
55
1
Order By: Relevance
“…This approach has been widely used in the literature. Altenbernd et al [17] showed that low-kVp images of DECT datasets are more sensitive in detecting hypervascular liver lesions, than the weighted average 120 kVp image series, but with a decrease in subjective image quality. With the advent of iterative reconstructions, Marin et al [18,19] showed the advantage of using iterative reconstruction when low kV is used.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been widely used in the literature. Altenbernd et al [17] showed that low-kVp images of DECT datasets are more sensitive in detecting hypervascular liver lesions, than the weighted average 120 kVp image series, but with a decrease in subjective image quality. With the advent of iterative reconstructions, Marin et al [18,19] showed the advantage of using iterative reconstruction when low kV is used.…”
Section: Discussionmentioning
confidence: 99%
“…17.1). In recent years, dual-energy and spectral CT technique has emerged, where the utilization of dual-source or polychromatic X-ray beams and the differential attenuation of such beams of different energies in tissues are applied to improve the detection of hypervascular hepatocellular carcinomas [14] or for the quantification of hepatic iron content [15]. However, dual-energy CT technology is still not widely employed in clinical practice despite potential merits, in part because of the post-processing time required to generate the appropriate images.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…By virtue of the nature of radiation attenuation, the contrast-to-noise ratio of HCCs in late arterial-phase images taken at 80-kVp can be better than those at 120-kVp, even though the overall noise level is higher in 80-kVp images than in 120-kVp images [28,29] (figs. 2, 3).…”
Section: ) Low-tube-voltage Ct Imagingmentioning
confidence: 99%
“…According to a previous study, these postprocessed image sets may improve evaluation of the therapeutic response of HCC to radiofrequency ablation and may also lead to lower radiation doses if precontrast CT scans can be replaced by virtual noncontrast images [36]. Given that iodinated contrast material provides greater X-ray attenuation at low tube voltage settings through an increased photoelectric effect, it is expected that low-kVp images of dual-energy datasets will be more sensitive than high-kVp images in detecting hypervascular liver lesions such as HCC, despite the higher noise levels [28]. As an alternative approach for improving detection of hypervascular HCC on CT, fused images can be created by blending the CT datasets obtained at different tube energies [37].…”
Section: ) Low-tube-voltage Ct Imagingmentioning
confidence: 99%